THE CREATIVE PROCESS OF 2D ANIMATION FROM SAND PAINTING BASED ON PERCEPTION THEORY - Leerasiri, Sompong (Fine Arts Journal: Srinakharinwirot University, 2026)
Background and Objectives: This study aims to develop knowledge and a creative process for producing 2D animation from sand painting through theories of perception. It examines the relationships among sand as a material, image-making techniques, frame-by-frame movement, and viewers’ perceptual mechanisms. The study culminates in the creative artwork “The Great King of King Rama IX”, which presents the royal aspirations and royal initiatives of His Majesty King Bhumibol Adulyadej through sand painting animation. Methodology: This research employs qualitative and creative research approaches. Data were collected from documents, research articles, online sources, and the works by five artists related to 2D animation, sand painting, and 2D painting. The analysis focuses on three aspects: content, form, and technique. The conceptual framework integrates Gestalt theory, visual perception, 2D animation theory, contemporary media concepts, and aesthetics to inform sketch development, storyboard design, and the production process. Key Findings: The creative process consists of four distinct stages: 1) preparation and sketch design; 2) preparation of materials, equipment, lighting, camera, and the work surface; 3) sand painting production and image recording; and 4) exhibition of the completed 2D animation. The final work is eight minutes long and is structured into eight sections based on the Noble Eightfold Path. Sand functions as a medium for image construction, transformation, and symbolic communication. Significance of the Study: The study demonstrates that sand painting can be developed into a contemporary moving-image medium that systematically integrates visual art, storytelling, technology, and perception theory. Perceptual principles, such as figure–ground relationship, closure, continuity, and texture perception, enable viewers to interpret incomplete forms, visual transitions, and cultural meanings with greater clarity Conclusion and Future Research Directions: Creating 2D animation from sand painting is a mixed-media process that requires a dynamic interrelation among concept, content, material, technique, visual timing, and audience perception. This study provides a foundational knowledge base for further developments in sand painting, 2D animation, contemporary media art, and the application of emerging technologies such as AR/VR in creative practice.